Fuzzy based battery energy storage system and braking resistor for mitigation of shaft-torsional oscillations - Mohamed Fayez Ahmed (Elsevier, 2021)
Autoreclosure is an irreplaceable protective scheme that was initially engineered for power system stability enhancement especially in areas with high isokeraunic levels. Unsuccessful reclosure on transmission lines emanating from thermal power plants has been long identified as a potential hazard to the shafts of the turbine-generators in these power plants. Therefore, the principal focus of this work is to mitigate the shaft torsional oscillations resulting from unsuccessful reclosure. The main scope of this study is to utilize a battery energy storage system controlled via fuzzy logic controllers to mitigate shaft torsional oscillations resulting from unsuccessful reclosure. Additionally, a coordinated operation of fuzzy based dynamic braking resistor is considered to obtain a superior torsional torque profile. Local control input signal synthesized from the generator shaft speed is employed in this work for the proposed controllers. For testing the effectiveness of the proposed scheme, non-linear time-domain simulation study is performed on a single machine infinite bus and the IEEE 3-machine 9-bus system via MATLAB/Simulink-based modelling and simulation platform. Comparative simulation studies of the test systems after being subjected to unsuccessful reclosure of three-phase to ground fault conditions demonstrate the effectiveness of proposed scheme. From the time domain simulation results, the torsional torque profiles reach an excellent level due to the implementation of the proposed scheme.